Synthesis and characterization of RPET/organo-montmorillonite nanocomposites - Basilia, Blessie A. (Philippine Engineering Journal)
Recycled polyethylene terephthalate (RPET)/organo-montmorillonite noncomposites were synthesized by direct melt intercalation method. The effect of this processing technique in the nanomorphology, thermal stability and mechanical behavior of the intercalated products were characterized by X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), small angle x-ray scattering (SAXS), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and mechanical analysis. The difference of using recycled PET (RPET) vis-a-vis virgin PET (VPET) as matrix in the polymer nanocomposites, using synthesized Philippine organo-montmorillonite or commercial organoclay as the layered-silicate, was evaluated. Results showed that direct melt intercalation by twin-screw extrusion method gave generally exfoliated structures especially at <5 percent clay loading, based on powder XRD patterns. SAXS patterns and HRTEM micrographs revealed laminated structures at the basal (001) reflections resulting to a d-spacing of 14 nm in localized areas not observed by powder diffraction. Higher levels of orientation of the layered silicates were obtained with commercial organoclay compared with the synthesized clay. Thermal degradation has been decreased and tensile strength increased with the increase in clay loading. RPET resin was intercalated in a similar manner with VPET in the layered silicates of Philippine organo-montmorillonite.